(3bhJ GdbdhHs - (3CHh WGdH Gdecj , eMeO Hf Ydj Hf YWjI GdMGQKj, CHh WGdH Gdecj,J (B386 (3g` s
(3ChdgG (B:s
(3TQM ebGe GdTcQ hCh UGa GdTGcQjf hgh GdKGdK ef ebGeGJ Gdjbjf s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdKGfis
(3GdChQGb ef (B176-225 (3cJHJ HNW MOjKs
(3GdeLdO GdKGfi ef TQM ebGe GdTcQ hChUGa GdTGcQjfs
(3hgh GdKGdK ef ebGeGJ Gdjbjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs